CARACTÉRISATION DE LA FLORE DE LA FORÊT D’ACHEMECHE POUR UN AMÉNAGEMENT INTÉGRÉ ET UN DEVELOPPEMENT TERRITORIAL DURABLE DE LA COMMUNE RURALE DE RAS JERRY / PROVINCE D’EL HAJEB /MAROC - Ikram ELMzaiti; Nasser-Eddine Zine; Ahmed Boukil (European Scientific Journal, ESJ, 2014)
The forest of Achemeche is the indispensable support of the framework of life and of the natural resources of the rural commune of Ras jerry, it constitutes the back country of the territory which our major objective is to integrate it into the integrated management and sustainable territorial development of the commune. The diversity of its flora is located weakened more and more because of the significant pressures due to human and urban activities, a state of knowledge of its plants and its remarkable wildlife in a prime time will allow us to provide scenarios for their preservation, conservation and valorisation in a sustainable manner.